How Customers Choose Hotels - Hera Oktadiana; Andhika Kurnia (Binus Business Review, 2011)
In the advancement of hospitality industry, thus it is important for hotel sales and marketing to understand the customer behavior in order to create effective marketing. Factors that influence customer behavior as individuality consist of personal and interpersonal factors. Personal factors include the needs, wants, motivation, perception, learning, personality, lifestyle, and self-concept. Meanwhile, interpersonal factors come from culture and sub-culture, group references, customers through stages before deciding to purchase. Begin with the awareness about the needs, customers then find information about the product or service that could be used to solve the problems. After having the information, customers select the best product and service before deciding to purchase. After purchasing, the last stage is evaluation of product and service, whether it is satisfying or not.